Respuesta :

Answer:

I think it would be more beneficial to know how to do these then know the answers since it's quite a simple concept.

Step-by-step explanation:

You take the number outside of the parentheses(if it's just a minus sign it's a negative 1) and multiply it by the number before the plus, minus, division, or multiplication sign. You multiply it by the number after. Then do the problem from there. I'll do the first one for you. 6 times 2n equals 12n. 6 times negative 9 is -54. So your answer is 12n - 54. Hope this helps.

Answer:

1)12n - 56

2)6n + 21

3)-12 n -16m

4)-8m + 4

5)9 - 12y

6)-6c +12

Step-by-step explanation:

6(2n - 9) = (2n x 6) (-9 x 6) = 12n - 56

3(2n + 7) = (2n x 3) (7 x 3) = 6n + 21

-4(3n+4m)= (3n x -4) (4m× -4) = -12 n -16m

-(8m -4)= -8m +4

3/4 (12 - 16y )=(12 x 0.75) (-16x 0.75) = 9 - 12y

-2(3c-6)= (3c x -2) (-6 x -2) = -6c +12

ACCESS MORE